Judicial function and the commons: the contribution of legal deontology - Sartea, Claudia (2012)
The article attempts to provide an in-depth study of the concept of profesional deontology with the aim of updating it and allowing it to break free from a crisis of ethics and sense of justice that seems overwhelming. At present, a number of perspectives have been disseminated that strip the work of professionals (the work of legal professionals and particularly of judges as well) from any reference to a common good, reducing it, according to each case, to a simple relationship between persons (more or less economically relevant), whereby everything is subject to negotiation or to the manifestation of a public power that controls and regulates all things, paradoxically ending up by removing the professional liability. The very concept of profesional work must be studied in depth, particularly with respect to the idea and specific function of the professions involved in the administration of justice until we achieve a professional work model, in which the person who exercises it, will know and perceive that it is their personal identity which is at stake: only then rules will make sense and achieve their purpose, which is to encourage everyone to conscientiously develop their social role and participate in the attainment of the common good